Drug Sequestration in Lysosomes as One of the Mechanisms of Chemoresistance of Cancer Cells and the Possibilities of Its Inhibition - Hraběta, Jan; Belhajová, Marie; Šubrtová, Hana; Merlos Rodrigo, Miguel Angel; Heger, Zbyněk; Eckschlager, Tomáš (International journal of molecular sciences, 2020)
Resistance to chemotherapeutics and targeted drugs is one of the main problems in successful cancer therapy. Various mechanisms have been identified to contribute to drug resistance. One of those mechanisms is lysosome-mediated drug resistance. Lysosomes have been shown to trap certain hydrophobic weak base chemotherapeutics, as well as some tyrosine kinase inhibitors, thereby being sequestered away from their intracellular target site. Lysosomal sequestration is in most cases followed by the release of their content from the cell by exocytosis. Lysosomal accumulation of anticancer drugs is caused mainly by ion-trapping, but active transport of certain drugs into lysosomes was also described. Lysosomal low pH, which is necessary for ion-trapping is achieved by the activity of the V-ATPase. This sequestration can be successfully inhibited by lysosomotropic agents and V-ATPase inhibitors in experimental conditions. Clinical trials have been performed only with lysosomotropic drug chloroquine and their results were less successful. The aim of this review is to give an overview of lysosomal sequestration and expression of acidifying enzymes as yet not well known mechanism of cancer cell chemoresistance and about possibilities how to overcome this form of resistance.
Keywords: V-ATPase inhibitors; Lysosomes; regulace genové exprese u nádorů; Humans; lysosomal sequestration; metallothioneins; Antineoplastic Agents; lidé; chemorezistence; exocytóza; vakuolární protonové ATPasy; V-ATPase; lysosomotropic agents; Neoplasms; Hydrogen-Ion Concentration; Exocytosis; nádorové buněčné linie; protinádorové látky; nádory; chemoresistance of cancer cells; lyzozomy; Cell Line, Tumor; koncentrace vodíkových iontů; Gene Expression Regulation, Neoplastic; Vacuolar Proton-Translocating ATPases; Drug Resistance, Neoplasm